Investigating the determinants and integrated relationships of corporate social responsibility within the global sypply chain ; a comparatie study between Thailand and Bangladesh garment sectors - Hossain, Tareq Bin (Prince of Songkla University, 2022)
This study aims to investigate the influence of multiple stakeholders on suppliers' social responsibility (SSR based on data from the apparel industry of Thailand and Bangladesh A two-stage conceptual model, basic and extended, was developed using stakeholder relational and multiplicity perspectives adapted from Neville and Menguc (2006) and Rowley (1997) The present study provides an empirical investigation of networked stakeholder relationships Buyer Pressure, Media Interest, Government Policy and Top Management Commitment, both individually and collectively on SSR behavior. ㆍFace to face and drop off and collect' survey administration techniques were used to collect a total of 371 questionnaires, where 137 data from the executives of Thai textile and 234 data from the executives of Bangladeshi garment sector. Partial Least Square (PLS) structural equation modeling combined with resampling and bootstrapping techniques to test the significance of the regression coefficients, were used to examine the hypotheses included in both basic and extended models. The findings suggest that while Buyer Pressure, Media Interest and Top Management Commitment, individually have positive relationships, only Media Interest and Top Management Commitment have a significant influence on SSR When complex interactions and mediation among stakeholders were considered, a thicker and a thinner pathway or network of stakeholders, indicating strong and weak network intluences on SSR. were detected The findings show that Media Interest. Buyer Pressure, Government Policy, Top Management Commitment and SSR constitute the thickest pathway compared with alterative pathways. Additionally, it was found that Buyer Pressure and Top Management Commitment displayed the most important network path mediation roles in moderating the networked influence on SSR While early studies explored individual stakeholder influence on SSR based on dyadic relationships among stakeholders and business, the present study contributes to an understanding the influence of a networked relationship among key stakeholders on SSR While top managements make SSR strategic decisions in managing stakeholder networks, they do not necessarily consider each stakeholdersㆍ claim or interest. The ability to influence SSR, a cause of recent ethical concern among business, is through networked relationships.